Meaning and Perceptions of the Good Life in Ghana - Dzokoto, V.A.; Osei-Tutu, A.; Scollon, C.N.; Wallace, D.; Peters-Chitwood, L. (Psychological Studies, 2019)
This experimental study extends the geographical focus of empirical investigations of what makes life good to Ghana, West Africa. Data were collected from a sample of 189 Ghanaian college students (19–49 years old). A 2 (income: high vs. low) × 2 (happiness: high vs. low) × 2 (meaning: high vs. low) experimental design was used to investigate factors related to judgements about the good life. Multivariate analysis of variance was used to test the study’s hypotheses. The results highlighted that similar to previous research, concepts of happiness and meaning are central to the conceptualization of the good life in Ghana. Unlike previous studies however, quality of life, desirability, and perception of the good life were not significantly intercorrelated. The findings suggest that while some factors may consistently predict the good life across diverse cultural settings, complementary consideration of culturally constructed meaning systems may be warranted.
Keywords: Africa; Good life; Happiness; Meaning; Well-being